MINISTRY OF HIGHER AND SECONDARY SPECIALIZED EDUCATION OF THE REPUBLIC OF UZBEKISTAN ACADEMIC LYCEUM UNDER TASHKENT TEXTILE AND LIGHT INDUSTRY INSTITUTE DEPARTMENT OF FOREIGN LANGUAGES ARTICLE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the connection between psychology and foreign language education, focusing particularly on lyceum students in Uzbekistan. It argues that psychological knowledge is not only helpful but essential in improving students' English language acquisition. The paper highlights three main psychological components—emotional intelligence, motivation, and self-awareness—as critical factors that significantly affect the learning process.